Meltwater Flowthrough Snow from Plot to Basin Scales - Williams, Mark; Pfeffer, W. T. (2001)
This supplement provided funds to purchase two pieces of equipment for research in snow hydrology: a high-precision temperature instrument suitable for snow and two Denoth snow-wetness meters. Contract supplements DAAH04-96-1-0033.